Ocular manifestation in progeria: A case report - Suwal, Rinkal; Dhakal, Pranita; Joshi, Purushottam (Nepalese Journal of Ophthalmology, 2020)
Introduction: Progeria also known as Hutchinson Gilford Progeria Syndrome (HGPS) (MIM176670) is a very uncommon fatal genetic untimely aging syndrome. It is characterized by retarded physical development, accelerated degeneration of the skin, cardiovascular and musculoskeletal abnormalities. Other features include prominent eyes, thin nose, small chin and thin lips. Eyebrow hair loss, madarosis and lagopththalmos are the common ocular manifestations.Case: We report a case of five year old boy with complaints of discomfort in bright light and a whitish appearance in his right eye for two months. He was accompanied by the parents. They complained of loss of eyelashes and eyebrows. In the developmental history he was normal at birth till the age of one year then they noticed gradual hair fall, delayed growth, wrinkling of skin, increase in size of head and thinning of limbs.Conclusion: This is the first case report from Nepal with the ocular presentation of progeria indicating the role of ocular senescence in patients with Hutchinson Progeria Gilford Syndrome.